Deforestation, development, and government policy in the Brazilian Amazon: An econometric analysis - Lykke E. Andersen; Eustáquio José Reis (Institute for Applied Economic Research (ipea), 2015)
This paper develops a model of deforestation and economic development in the Amazon. It is based on the determinants of demand for agricultural land, i.e. on the interactions between population dynamics, urbanization and the growth of local markets, land prices, and government policies. The model is estimated using a panel data set covering 316 municipalities in the Brazilian Amazon during the period 1970/85. The model is used to evaluate the effects of different policy instruments. The trade-off between economic growth and deforestation is shown to be quite good for subsidized credit but very bad for new road building.
Keywords: 330